Effects of training, environment, and host factors on the sweating response to exercise - Armstrong, L. E.; Maresh, C. M. (International Journal of Sports Medicine, 1998)
Because metabolic heat production is proportional to the amount of work performed, the differences in core body temperature (Tcore) of humans exercising at similar absolute exercise intensities are due to differences in their efficiency of heat dissipation. The purpose of this paper is to delineate the effects of training status, heat acclimation, environmental conditions and host factors on the sweating response to exercise. These factors are reviewed in light of their effects on the biophysical enhancement or suppression of sweating, and modifications of the relationship between local sweat rate and Tcore (degrees C). Athletes are advised to optimize those factors that enhance, and eliminate those factors that diminish, the onset and responsiveness of sweating.